1996
DOI: 10.1016/s1078-5884(96)80281-4
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative heparinisation, blood loss and myocardial infarction during aortic aneurysm surgery: A joint vascular research group study

Abstract: Heparin does not increase blood loss or the need for blood transfusion during surgery. Heparin is not necessary to prevent distal thrombosis when the aorta is cross clamped. The results of the study are consistent with the known mechanisms leading to intraoperative MI and strategies for its prevention. Intravenous heparin, given before aortic cross clamping, is an important prophylaxic against perioperative MI in relation to AAA surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 5 publications
1
55
0
1
Order By: Relevance
“…The possibility of increased bleeding with heparin and, perhaps more importantly, worries about toxicity and the direct anticoagulant effects of protamine sulfate, have led many surgeons to avoid heparin altogether [4]. Additionally, heparin is not necessary to prevent distal thrombosis during aorta cross clamping [5]. However, Thompson and colleagues [5] reported that heparin did not increase blood loss or the need for blood transfusion during replacement of an AAA and was an important prophylactic agent against peri-operative myocardial infarction in relation to replacement of an AAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of increased bleeding with heparin and, perhaps more importantly, worries about toxicity and the direct anticoagulant effects of protamine sulfate, have led many surgeons to avoid heparin altogether [4]. Additionally, heparin is not necessary to prevent distal thrombosis during aorta cross clamping [5]. However, Thompson and colleagues [5] reported that heparin did not increase blood loss or the need for blood transfusion during replacement of an AAA and was an important prophylactic agent against peri-operative myocardial infarction in relation to replacement of an AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, heparin is not necessary to prevent distal thrombosis during aorta cross clamping [5]. However, Thompson and colleagues [5] reported that heparin did not increase blood loss or the need for blood transfusion during replacement of an AAA and was an important prophylactic agent against peri-operative myocardial infarction in relation to replacement of an AAA. The patient had a medical history of axillo-femoral bypass, PTCA, and CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Aforementioned transformation includes: the inflammation and neovascularization [25], proteolytic activity [26] -especially increase in elastase production [27], decrease in collagen synthesis [28][29][30] and production of abnormal collagen [29]. From the clinical point of view, rapid growth and volume of ILT is correlated with the high risk of rupture [31].…”
Section: Presence Of Intraluminal Thrombus and Calcifications In Aaa mentioning
confidence: 99%
“…The safety of intraoperative heparin administration during vascular surgical procedures has been demonstrated in large studies (109). Heparin is usually given intravenously and during open AAA repair is typically administered 2-3 minutes before cross-clamping the aorta.…”
Section: Intraoperative Anticoagulation and Other Pharmacologymentioning
confidence: 99%